ISOL Exploring the relationship between English teachers’ beliefs and their practices in implementing the Merdeka Mengajar platform - Ali Mahfud; M. Bahri Arifin; Desy Rusmawaty; Ventje J Kalukar; Sunardi Sunardi; Syamdianita Syamdianita (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2026)
Merdeka Mengajar Platform (MMP) was released to support the implementation of the Merdeka Curriculum. While this platform aims to improve teacher competence and learning effectiveness, research into the extent to which English teachers adopt and practice MMP is limited. Therefore, this study aims to analyze English teacher's beliefs and practices in implementing MMP, identify the alignment and misalignment between beliefs and practices, identify the challenges faced, and explore the strategies used in adapting teaching practices to MMP principles. This research used a qualitative approach with a case study design. Data were collected through semi-structured interviews, classroom observations, and analysis of learning documents. The results showed that English teacher has a positive belief in MMP as a useful tool in improving pedagogical skills, facilitating differentiated learning, and enriching teaching methods. However, there were challenges in implementing MMP include low active student participation, limited facility support, and varying levels of teacher understanding of the platform. To overcome these challenges, the English teacher applied strategies such as the use of diverse learning media, differentiated assessments, and intensive communication with parents. The results of this study confirm the need for continuous support in the form of professional training and provision of adequate infrastructure to optimize the use of MMP. Further studies are recommended to examine the long-term impact of MMP on teaching effectiveness and student learning outcomes in English language learning.